Der Ablauf der Jahreszeiten in Japan aus der Sicht der Witterungsklimatologie und seine Bedeutung für das japanische Leben - Yazawa, Taiji (ERDKUNDE, 1980)
In the present paper the author traces weather trends in each season and then points out by examples how they have something to do with Japanese life. On the standpoint of weather climatology he divides a year into winter, summer and two transitional seasons, of which the one is between winter and summer and the other summer and winter. The former is subdivided into spring, early summer and bai-u (rainy season), and the latter shurin (rainy season) and autumn respectively. In order to make clear the weather trends in each season and its regionalities the author draws the so-called weather diagram, using the observed data at the following four stations: Sapporo(northern Japan), Tokyo (on the Pacific side of central Japan), Kanazawa (on the Japan Sea side of central Japan) and Naha (south western Japan). Four climatological elements are used to draw each weather diagram, namely the max. and min. temperature, direction of the strongest wind and amount of precipitation on each calendar day in the recent year,1978. He analyses these diagrams, mainly, paying attention, however, to another year, because weather trends in each season are different from year to year. The results not only of the weather trends and their regional differences in that year but also in other cases are concretely pointed out; moreover various unusual weather trends, such as the cool summer in northern Japan, drought in western Japan, typhoons, foehn on the Japan Sea side, occurrence of killing frosts etc., are clarified. On the basis of such results the author makes clear by several examples that the correspondence of Japanese life to weather trends has changed, or is changing now, with the times in company with industrialization, urbanization and modernization of Japanese life.